EXPERIMENTAL STUDY OF INTERACTION SHALE-FLUID THROUGH IMMERSION TESTS - Rabe, Claudio; da Fontoura, Sérgio Augusto Barreto; Antunes, Franklin dos Santos (Revista de Engenharia Térmica, 2002)
The present work has as objective the study of the behavior of preserved shale samples when immersed in aqueous solutions. The obtained results show that the solutions presented high variations of pH, salinity and electric conductivity, what indicates ionic migration of salts from the rock to the fluid, and small variations of Redox potential. Chemical analysis indicate strong migrations of ions from the rock to the fluid. It can also be observed that the solutions become cloudy, denser and more viscous. Besides, the samples suffer elevations of its water content, small variation of its cation exchange capacity and chemical composition, loss of solid material from superficial disintegration and the development of fractures in the cores. This work contributes to the understanding of the shale behavior in presence of drilling fluid water base.